The construction of family values in geopolitical discourse: the ongoing legacy of Adolf Hitler and Britain's 'supreme emergency'. Issue 1 (8th March 2013) - Flint, Colin
<x xml:space="preserve">Abstract</x> The use of the philosophical axioms of just war theory by political leaders justifying their participation in war is examined. Especially, the just war themes of 'supreme emergency' and 'emergency ethics' are investigated as a means of justifying extra‐territorial wars, or wars that are far away from a state's borders and where no imminent threat of invasion is present. The practice of equating geopolitical situations to the actions of Hitler and Nazi Germany is seen as a consequence of the mobilisation of the language of 'emergency ethics'. The rhetoric justifying extra‐territorial warfare uses an idealised sense of the home that is reinforced by the practices of soldiers. Furthermore, the importance of values in the 'emergency ethics' logic is investigated by exploring the memoirs of a British Army chaplain serving in the Korean War. The contemporary relevance of the article lies in the extra‐territorial nature of the War on Terror and the persistent use of reference to values to justify immoral and illegal acts of war.